La implementación de un régimen especial de insolvencia para las MYPE - Lizárraga Vera-Portocarrero, Anthony (2016)
In Peru, small companies have many difficulties to access financial services; therefore, a possible solution is to have a special regime for these companies, which grants a higher expectative of payment to creditors compared with the traditional bankruptcy system, because this access to services provided by financial intermediaries becomes essential for the stability and progress of the sector.